Describing the employer’s satisfaction on college of business education graduates employed in banking institutions - Benitez, Ritchie Jean Jie Lizza; Balmadres, Reycillame; Panoril, Zaldie Boy II; Alfanta, Mylene; Naparan, Janus (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
This study evaluates the employer’s satisfaction with the banking institutions in Pagadian City. Employers’ satisfaction will be based on how the graduates show their performance towards their jobs or tasks. Employers evaluate the skills of the graduates that need to be improved in their daily tasks. This study uses the quantitative-descriptive study approach to analyze information about describing the employer’s satisfaction with the graduates. The study’s primary purpose is to find out how satisfied employers are with the performances of the graduates as well as what is needed to improve. It focuses on the employers of the banking institutions as research participants. The findings of the study are as follows: (1) foundation skills, (2) enterprise skills, (3) technical skills and knowledge, (4) adaptive skills, (5) team-working skills, and (6) employability skills where these are used in getting the satisfaction of the employers to the graduates where it garnered an overall weighted mean of 3.34 and a standard deviation of 0.01 with an interpretation of ‘very high’. The results showed that the employers of the banking institution where the graduates are employed are very satisfied with the performance that the graduates showed to them. In addition, the employers highlighted some skills that need to be developed and improved more to become efficient and effective employees. The results of this study can be used as a basis for the development of the graduates to enhance their performance in the future.